PHYSICAL WATER QUALITY CONTAMINATED BY SOIL-TRANSMITTED HELMINTHS IN SUMBERSARI DISTRICT, JEMBER REGENCY - Laily Nurhayati; Wiwien Sugih Utami; Muhammad Afiful Jauhani; Yunita Armiyanti; Bagus Hermansyah (Universitas Airlangga, 2022)
Introduction: Soil-Transmitted Helminth (STH) or worm infection is an infection caused by intestinal nematode worm group that can be infectious through the soil medium. One straightforward transmission route is through contaminated water consumption as water is needed daily. This study aims to know the association between quality of physical water and STH contamination in the Sumbersari District, Jember Regency, water sources. Methods: This research is an analytical observational study with a cross-sectional design. Data was obtained from water physical quality inspection and STH contamination in the water laboratory. The 30 samples were taken purposively. Results and Discussion: The results of the data analysis of the association between water temperature and STH contamination showed a p-value of 0.014, the association between watercolor with STH contamination showed a value of 0.566, and the association between odor and TDS of water with STH contamination was not analysed. Statistics analysis results showed a significant association between the quality of water physics and STH contamination in the water sources in Sumbersari District, Jember Regency, with a score of 0.022. Conclusion: The physical quality of water has a positive correlation with STH contamination in water sources in Sumbersari District, Jember Regency.